STUDI DRAMATURGI: ANALISIS PENGELOLAAN PENGADAAN BELANJA MODAL KONSTRUKSI DI KEMENTERIAN KEUANGAN - Resi Ariyasa Qadri (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2020)
This case study explicates dynamics of public procurement spectacle in The Ministry of Finance of The Republic of Indonesia for period of 19 months. The main focus of this paper is to provide deeper investigation to answer 3 research question: (1) what really happened in public procurement practice in The Ministry? (2) how did the actors respond to the dynamics of decision making process in the practice of public procurement? (3) how may the actor’s responses be rationalised? This paper was based on semi-structured interviews with 29 key actors in the practice of public procurement in The Ministry to complement the participant observation data of vendor selection process in 11 procurement packages, either in central office or in local offices. This study implements Goffman’s dramaturgical framework to examine the role of actors, region, performance, plot, or impression management in the field of public procurement of The Ministry, while the logic of appropriateness framework was used to portray the nature of actor’s action. Our findings succeeded to unveils “the two faces” behaviours and impression management performed by the vendor as they also managed to unravel the fact of rule based action performed by the actors of public procurement practice in The Ministry.